Effects of feeding high volumes of milk replacer on reproductive performance and on concentrations of metabolites and hormones in blood of Japanese black heifer calves. (13th January 2021) - Taguchi, Yutaka; Inabu, Yudai; Hayasaki, Koki; Maeda, Noriyuki; Kanmera, Yoshiro; Yamasaki, Seiji; Ota, Noboru; Mukawa, Kenji; Tsuboi, Arisa; Miyamoto, Hirokuni; Etoh, Tetsuji; Shiotsuka, Yuji; et al.
Abstract: We evaluated the effects of feeding high volumes of milk replacer on growth and reproductive performances in Japanese black heifers. Fifty‐one heifers were fed milk replacer at 9 L/day for 60 days (9 L × 60 days; n = 18) or 41 days (9 L × 41 days; n = 15), or at 7 L/day for 40 days (7 L × 40 days; n = 18). Artificial insemination (AI) was performed on heifers with ≥270 kg body weight and ≥116 cm body height at 300 days of age. The age at the first AI was 0.35 month later for 7 L × 40 days than the other groups ( p < .01). However, age at calving did not differ among treatments (22.1 months). The interval from the first AI to pregnancy tended to be 2 months longer for the 9 L × 60 days than the other groups ( p = .07). Our results showed that feeding high volumes of milk replacer may reduce the age at calving via an improved rate of growth. In addition, we propose that feeding a maximum of 7 L milk replacer for 40 days may be the most appropriate rearing regime because the success of pregnancy per AI may be reduced in calves fed a maximum of 9 L for 41 and 60 days.